Nurses Who Assume the Role of Advocate for Older Hospitalized Patients: A Qualitative Study - Luca, Corina Elena (SAGE Open Nurs, 2021)
INTRODUCTION: Patient advocacy, acting on behalf of patients’ unmet needs, is fundamental to nursing, and the perception of the need for advocacy motivated this study. Nurses experience moral discomfort, which results from a divergent view regarding medical or caregivers’ decisions about patients’ clinical proceedings, in which patients’ involvement in making those decisions is either doubtful or absent. OBJECTIVES: The aim of this study is to assess the need for advocacy and explore the perspectives of nurses engaged in the care of older patients. METHODS: The methodological orientation is that of a qualitative design, by using a purposive and criterion sampling. The sample was of 14 nurses of a ward of general medicine. Focus group as collecting data tool was used, followed by a thematic analysis. RESULTS: Nurses demonstrated a high level of moral sensitivity to ethical problems in clinical practice and on occasions, the courage to bring the problem to the physicians or patients’ family’s attention, or help patients develop self-determination. However, it is difficult to advocate because of insufficient communication between professionals, insufficient knowledge of ethics, and the emotional burden it places on nurses which results in emotional resignation in the face of interprofessional teams’ lack of consideration of nurses’ opinions. CONCLUSION: This research highlighted nurses’ need for advocacy to promote patients’ rights, wishes, and values. It is essential for nurses to be aware of their level of moral sensitivity and develop a strategy to regain courage to engage in advocacy. Therefore, ethics education and interprofessional ethical leadership is desired, which inspires healthcare professionals’ work and allows the foundations of an ethical decisionmaking process to be laid through patients and their families’ active involvement.